Importancia del hongo entomopatogeno Beauveria bassiana en el control de insectos plaga en cultivos de hortalizas en la provincia de Los Ríos - Ramírez Vergara, Jefferson Joel (2020)
The present work tries to know the importance of the entomopathogenic mushroom Beauveria bassiana in the pest insect control on the cultivation of vegetables in the province of Los Ríos. Also, to show their behavior, structure, and the efficiency of this mushroom on vegetables considering the environmental impact that this would cause. The present study is based on scientific researcher related to the proposed topic in certain vegetable, those adaptable to warm climates and those that aren´t from warm climate. As we know “Ecuador is divided into three big geographic regions: coast, mountain range and east. The 86% of the surface dedicated to horticulture is in the mountain range, the 13% is on the coast and only the 1% is in the east”. (FAO) Having said that, the information below will serve as a bridge for various investigative works that will be based on from that.